2002
DOI: 10.1073/pnas.232480899
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular corticotropin-releasing factor increases limbic glucose metabolism and has social context-dependent behavioral effects in nonhuman primates

Abstract: Corticotropin-releasing factor (CRF) is a neuropeptide involved in integrating the behavioral, autonomic, and hormonal responses to stress within the central nervous system. Patients suffering from depression have abnormal activity in stress responsive brain regions and elevated cerebrospinal fluid CRF. The DSM-IV criteria for major depressive disorder include behavioral changes such as depressed mood, anhedonia, and psychomotor agitation͞retarda-tion. We studied the effects of 434 g of CRF given intracerebrov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 37 publications
(39 reference statements)
0
42
0
Order By: Relevance
“…Such studies reveal that 30 to 60 min after the onset of a stressor, molecular markers of neural activity in multiple structures are increased (e.g., cFos, nerve-growth factor-induced protein A), suggesting a stimulating effect of stress on neural activity (33,34). In human beings, associations between neurobiological alternations in limbic areas and clinical symptoms have been reported previously in a number of psychological disorders, such as PTSD (8), social anxiety disorder (35), specific phobia (35), and depression (36). In addition, our study identified decreased functional connectivity among distributed limbic-striatal and default-mode networks in the survivor group, reflecting functional disconnections across the brain (37).…”
Section: Discussionmentioning
confidence: 75%
“…Such studies reveal that 30 to 60 min after the onset of a stressor, molecular markers of neural activity in multiple structures are increased (e.g., cFos, nerve-growth factor-induced protein A), suggesting a stimulating effect of stress on neural activity (33,34). In human beings, associations between neurobiological alternations in limbic areas and clinical symptoms have been reported previously in a number of psychological disorders, such as PTSD (8), social anxiety disorder (35), specific phobia (35), and depression (36). In addition, our study identified decreased functional connectivity among distributed limbic-striatal and default-mode networks in the survivor group, reflecting functional disconnections across the brain (37).…”
Section: Discussionmentioning
confidence: 75%
“…Strome et al (2002) reported increased glucose metabolism in the amygdala, pituitary, and hippocampus concurrent with increases in plasma cortisol levels, plasma ACTH levels, and anxiety and/or depressive symptoms after ICV infusion of CRF in rhesus macaque. The interaction of the amygdala with the hippocampus, dorsal and ventral striatum, orbital frontal cortex, paraventricular nucleus of the hypothalamus, and midbrain (Charney and Drevets 2002;Davis 2005) may be relevant to the additional glucose metabolic changes observed in those regions.…”
Section: Discussionmentioning
confidence: 92%
“…Acute stress causes upregulation of CRF in amygdala (Stout et al, 2002). Stimulation of amygdalar CRF receptors, and consequent increase in amygdalar metabolic activity, results in increased anxiety-like and decreased pro-social behaviors (Strome et al, 2002;DeVries et al, 2002). CRF is also released in the frontal cortex, where it signals the salience of environmental cues (Merali et al, 2004).…”
Section: Discussionmentioning
confidence: 99%